Epidemiological Assessment of acute poisoning Death–One year Survey - Khodabandeh, Farideh; Emamhadi, M.A; Mostafazadeh, Babak (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background: Acute poisoning by drugs and chemical agents is a medical emergency and carries a high morbidity and mortality rate. The epidemiology of acute poisoning varies between countries and different regions. Method: In this one year retrospective study, we reviewed the epidemiology of patients with acute poisoning (intentionally or unintentionally) who died during hospitalization at Loghman Hakim hospital, Tehran, Iran. Results: Of the 280 cases of completed suicide by self-poisoning 69 (24.6%) cases were female and 211(75.4%) cases were male, between 15-78 years old with mean±SD of 39±17.5. Most of them were conscious (69.6%) on admission to Emergency Department (ED). Past history of any self- harm were positive in 82 (29.3) cases of subjects. Multiple drug toxicity and opioid poisoning were the most common causes of acute poisoning death in 27.5% and 27.1% respectively. Conclusion: Differences based on age category, sex, the types of toxic agents involved and the outcomes of the poisoning death incidents were noted. Future interventions should take these differences into account.